Anti-biofilm efficacy of root canal irrigants against in-situ Enterococcus faecalis biofilms in root canals, isthmuses and dentinal tubules. (December 2018) - Ye, Wei-hu; Fan, Bing; Purcell, Wiley; Meghil, Mohamed M.; Cutler, Christopher W.; Bergeron, Brian E.; Ma, Jing-zhi; Tay, Franklin R.; Niu, Li-na
Abstract: Objective: To investigate the anti-biofilm efficacy of root canal irrigants in canal spaces, isthmi and dentinal tubules of root canals ex vivo. Methods: Fifty-one single-rooted premolars, each containing an isthmus, were instrumented, autoclaved and inoculated with Enterococcus faecalis for 4 weeks. One specimen was sectioned for bacteria-specific staining to confirm the presence of biofilms using light microscopiy. The remaining specimens were randomly divided to five groups: (1) 0.9% NaCl, (2) SilverSol/H2 O2, (3) HYBENX, (4) QMix 2 in1, (5) 6% NaOCl. Bacterial sampling was performed before (S1) and after (S2) canal irrigation. Diluted bacteria suspension was cultured for 48 h for counting the colony forming units (CFU). Percentages of dead bacteria and biofilm thickness were evaluated by confocal laser scanning microscopy (CLSM). Metabolic activity, lactic acid and polysaccharide synthesis of E. faecalis derived from S2 samples were analysed. Results: The percentages of dead bacteria were significantly affected by the factor "irrigant" (p < 0.001) and the factor "location" (p = 0.017). The percentages of dead bacteria in the isthmi and canals were both in the ordor: NaCl < SilverSol/H2 O2 < HYBENX < QMix 2 in1 < NaOCl (p < 0.05). Only 6% NaOCl disrupted biofilms and significantly reduced their thickness. The CFU, metabolic activity, polysaccharide and lactic acid production of E. faecalis were all reduced by the disinfecting solutions. Conclusions: SilverSol/H2 O2 and HYBENX were less adept than QMix 2 in1 at killing biofilm bacteria in root canals. None of these antibacterial irrigants were effective, compared with 6% NaOCl, in disrupting biofilms. Clinical significance: There is advantage in using HYBENX or QMix 2 in1 to kill intratubular bacteria biofilms because of their capability in removing the inorganic component of the smear layer. SilverSol/H2 O2 requires extra time to eradicate intratubular biofilms upon removal of the organic and inorganic components of the smear layer by other root canal irrigants.